DETERMINANTS OF MANUFACTURING COMPANIES' STOCK PRICE IN THE PRIMARY CONSUMER SECTOR - Dewi Maya Sari; Mutia Arfiani; Patuh Mahyunda (Universitas Gunadarma, 2022)
This study aims to examine the factors that affect stock price changes using 328 samples of non-cyclical consumer manufacturing companies for the period 2013 to 2020. The factors tested in this study are liquidity, profitability and firm size. The data used is the company's annual financial report data that meets the criteria for determining the sample. Data analysis was performed using multiple linear regression. The results showed that liquidity, profitability and firm size had a positive and significant effect on stock price.